2016
DOI: 10.1007/s10461-016-1512-9
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sexual History Taking for PrEP Comprehension Among Young People of Color

Abstract: Despite demonstrated efficacy, uptake of pre-exposure prophylaxis (PrEP) remains low, especially among highest priority populations. This study examined four PrEP messaging factors hypothesized to impact comprehension of PrEP educational information: 1) modality (video versus in-person message delivery); 2) frame (risk versus health focus); 3) specificity (gist versus verbatim efficacy information); and 4) sexual history (administered either before or after PrEP education). We examined message comprehension am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…2,8 However, the disproportionate impact of the HIV epidemic has not led to higher PrEP interest, potentially due to the differential impact of structural barriers and/or stigma. [9][10][11] Regardless of the mechanism, higher interest among Black and Latinx men could support uptake of STI prevention strategies in communities that could benefit most. Furthermore, the remarkably high overall interest and willingness to participate in a randomized placebo-controlled trial suggests that doxycycline-PEP research interventions could have high accrual and acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 However, the disproportionate impact of the HIV epidemic has not led to higher PrEP interest, potentially due to the differential impact of structural barriers and/or stigma. [9][10][11] Regardless of the mechanism, higher interest among Black and Latinx men could support uptake of STI prevention strategies in communities that could benefit most. Furthermore, the remarkably high overall interest and willingness to participate in a randomized placebo-controlled trial suggests that doxycycline-PEP research interventions could have high accrual and acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…A U.S. study has shown that the experience of having a sexual history taken improved understanding about PrEP among young cisgender men, transgender women, and genderqueer individuals who reported condomless sex with a male partner. 37 Although sexual history taking is not performed routinely in health care settings in China, and may be particularly challenging to perform given the high stigma around anal sex, 38,39 taking a sexual history is a critical component of PrEP-related services. Providing training to provide MSMcompetent nonstigmatizing care is needed urgently.…”
Section: Discussionmentioning
confidence: 99%
“…22,[47][48][49][50] Although risk-framed messaging has been utilized widely in HIV prevention programs to facilitate uptake of prevention strategies such as testing, 51,52 our data suggest the importance of incorporating nonrisk-framed approaches to promote PrEP. One approach to help potential users identify their candidacy for PrEP is through gainframed messaging, 46,53 that is, to focus on health benefits that PrEP may bring rather than emphasizing HIV risks exclusively and framing PrEP as a targeted strategy for ''high-risk'' populations, 37,54 as has been done commonly in PrEP programs in the United States. Studies are needed to test the acceptability and appropriateness of gain-framed, sex-positive PrEP messaging strategies for MSM in the Chinese context.…”
Section: Discussionmentioning
confidence: 99%
“…Articles concerning the role of stigma understandably included historically stigmatized and under-served populations; nonetheless, future research is needed to fully understand the role of PrEP-stigma specifically and how PrEP-stigma manifests in all populations in need of HIV prevention. For example, in more recent studies [38, 40], the authors examined the influence of alcohol and drug abuse on patients’ beliefs and whether such beliefs influence PrEP uptake. These and other studies examining associations between alcohol and/or drug use and PrEP access, adherence, and discontinuation could also examine the influence of PrEP-stigma and thus further elucidate current understanding of stigma in the context of PrEP implementation.…”
Section: Discussionmentioning
confidence: 99%